DevSecOps into Multi-Cloud Environments for Resilient Application Development - Nadipalli, Rajesh (International Journal of Computing and Engineering, 2022)
The adoption of multi-cloud strategies presents significant opportunities for enhanced resilience, flexibility, and cost optimization. It also introduces substantial security and operational complexities. This article explores the integration of DevSecOps principles and practices into multi-cloud environments to foster resilient application development. I argue that a cohesive DevSecOps framework, tailored for multi-cloud intricacies, is essential for automating security, ensuring compliance, and enabling rapid, reliable application delivery. This paper examines the key challenges of managing security across disparate cloud platforms, including fragmented security controls, inconsistent identity and access management (IAM), and complex threat landscapes. I propose a unified DevSecOps pipeline that embeds security throughout the entire software development lifecycle (SDLC), from code inception to deployment and runtime. Key components of this framework include centralized security management, automated policy-as-code, continuous monitoring, and incident response across all cloud providers. Through a review of current literature and case studies, this article demonstrates how integrating DevSecOps in multi-cloud settings can significantly improve application resilience, reduce vulnerabilities, and enhance overall security posture. I conclude by offering a set of best practices and a strategic roadmap for organizations seeking to implement a successful and scalable DevSecOps model in their multi-cloud architecture.